Development and validation of instrument for assessing patients’ knowledge, attitude, and practice (KAP) on uncomplicated malaria management - Nanloh S. Jimam & , Nahlah E. Ismail, Maxwell L. P. Dapar (Journal of Applied Pharmaceutical Science, 2019)
Objectives: To develop and validate patients’ knowledge, attitudes, and practice instrument for uncomplicated malaria (PKAPIUM).Material and Methods: A draft PKAPIUM scale was developed after the review of relevant literature and malaria treatment guidelines, and six experts validated its content. Monte Carlo simulation principle was followed in arriving at 300 patients populations whose data were used to reduce the items based on “Kaiser’s eigenevalue-greater-than-one rule.” This was followed by the test of validity and reliability to assess the psychometric properties of the instrument.Results: The items content validity indices (I-CVI) and the scale CVI (S-CVI) using universal agreement (UA) within experts (S-CVI/UA) and average CVI (S-CVI/Ave) approaches were good (0.8–1.00), with absence of items’ floor or ceiling effects. Twenty-one items were retained in the new scale arranged under four factors with average variance extracted (AVE) and square root AVE values of 0.58–0.70 and 0.76–0.84, respectively, suggesting convergent and discriminant validities. The goodness-of-fit results [Chi-square (CMIN/DF) = 3.07, p = 0.00], standardized root mean square residual = 0.070, root mean square error approximation = 0.08 confirmed the hypothesized factor structures of the scale whose internal consistency of Cronbach’s alpha and composite reliability values were 0.74 and 0.82, respectively, and stability of ICC = 0.92 [95% confidence interval : 0.87–0.95, F = 43 (p = 0.51)].Conclusion: The validity and reliability of the PKAPIUM were in acceptable ranges.
Keywords: CFA, EFA, KAP, reliability, uncomplicated malaria.